Sentinel phenotype for rubella embryopathy: time-space distribution in Brazil - Iêda Maria Orioli; Jorge S. López Camelo; Monica Rittler; Eduardo E. Castilla
The dyad comprising eye anomalies and congenital heart defects in the same newborn has been proposed as the best sentinel phenotype for the early detection of rubella embryopathy. Time-space birth prevalence distributions of the eye-heart dyad were described in 36 Brazilian hospitals from the Latin-American Collaborative Study of Congenital Anomalies - ECLAMC network, for the period 1994-2008. Seventy dyad cases observed among 554,531 births showed seasonal variation (Χ2 = 5.84; p < 0.05), suggesting an environmental etiology, with an increase in cases in October-March and acrophase in December. The secular distribution of dyad prevalence rates was consistent with the distribution of rubella cases in Brazil, showing a decrease from 1994 to 2004, followed by an increase until 2008. Two geographic clusters were identified, one with high and the other with low dyad prevalence. In the high prevalence cluster, a secular increase was observed, starting in 1999, matching the rubella epidemic waves observed in Brazil in 1998-2000 and 2006.